WiFi-based Respiration Detection Aided by Intelligent Reflecting Surfaces - Yun WU; Dongheng ZHANG; Ganlin ZHANG; Xuecheng XIE; Fengquan ZHAN; Yan CHEN (Leida xuebao)
Since 2010, the utilization of commercial WiFi devices for contact-free respiration monitoring has garnered significant attention. However, existing WiFi-based respiration detection methods are susceptible to constraints imposed by hardware limitations and require the person to directly face the WiFi device. Specifically, signal reflection from the thoracic cavity diminishes when the body is oriented sideways or with the back toward the device, leading to complexities in respiratory monitoring. To mitigate these hardware-associated limitations and enhance robustness, we leveraged the signal-amplifying potential of Intelligent Reflecting Surfaces (IRS) to establish a high-precision respiration detection system. This system capitalizes on IRS technology to manipulate signal propagation within the environment to enhance signal reflection from the body, finally achieving posture-resilient respiratory monitoring. Furthermore, the system can be easily deployed without the prior knowledge of antenna placement or environmental intricacies. Compared with conventional techniques, our experimental results validate that this system markedly enhances respiratory monitoring across various postural configurations in indoor environments.